ANALISIS KEMAMPUAN PEMECAHAN MASALAH MELALUI PEMBELAJARAN TEAMS GAME TOURNAMENT BERBASIS DISCOVERY LEARNING - Maimunah; Sulistyorini, Yunis; Sunuyeko, Nurcholis; Rochsun (Universitas Insan Budi Utomo, 2022)
Students' mathematical problem solving ability in solving subject matter needs to be considered. This study aims to describe problem solving skills through discovery learning-based TGT learning for seventh grade students of SMP Ahmad Yani. This study used a qualitative research approach. The subjects studied were 3 students who were selected from 24 students in grade VII SMP Ahmad Yani based on the level of mathematical ability in participating in mathematics learning activities in class. Data collection techniques were observation models, written tests, interviews, and documentation. The results showed that: (1) Student who had high mathematical abilities was able to solve complex problems correctly Students' mathematical problem solving ability in solving subject matter needs to be considered. This study aims to describe problem solving skills through discovery learning-based TGT learning for seventh grade students of SMP Ahmad Yani. This study used a qualitative research approach. The subjects studied were 3 students who were selected from 24 students in grade VII SMP Ahmad Yani based on the level of mathematical ability in participating in mathematics learning activities in class. Data collection techniques were observation models, written tests, interviews, and documentation. The results showed that: (1) Student who had high mathematical abilities was able to solve complex problems correctly and carried out in a neat order of completion procedures. This means that students who have high mathematical abilities had excellent mathematical problem solving abilities. (2) Student who had moderate mathematical skills had good math-solving skills. Student was able to answer the problem correctly even though the work process incorrect. (3) Student who had low mathematical abilities was not able to solve problems properly and correctly, even tend to answer with messy results. This means that student who had low mathematical abilities had very low mathematical problem solving ability.